A mixed‐methods study of the quality of parental support during adolescents' information‐related Internet use as a co‐construction process - Kurock, Ricarda; Teichert, Jeannine; Meister, Dorothee M.; Gerhardts, Lara; Buhl, Heike M.; Bonanati, Sabrina (Journal of Adolescence)
Abstract Introduction In Europe, most Internet searches for school‐related tasks are situated at home, where parents can support adolescents. Although the frequency (quantity) of parental support has already been analyzed, a research gap exists concerning the quality of parental support in adolescents' information‐related Internet use. The quality of parental support in the field of homework involvement is known to be a predictor of adolescents' learning motivation and academic achievement, often discussed with regard to self‐determination theory (SDT) in terms of autonomy support, structure, emotional support, and control. These categories were adapted in this study to analyze parents' support in adolescents' Internet searching activities. Methods Using a mixed‐methods approach, we combined quantitative questionnaires and qualitative observations to analyze joint information‐related Internet uses. Therefore, 243 parent–adolescent dyads were surveyed and six parent–adolescent dyads were observed by videography in 2019/2020 in Germany. The adolescents were 11 years old, on average. Results The parents rated all qualities higher than the adolescents. Emotional support was rated highest by both groups, whereas structure was rated lowest. Adolescents' and parents' view on parental support differ. The qualitative study revealed parents' often interfering behavior, whereas emotional support was low. Further, the active role of adolescents was highlighted in both quantitative and qualitative data. Conclusions By combining quantitative and qualitative approaches, we demonstrated a fruitful application of SDT in analyzing the quality of parental support during adolescents' Internet searches at home and shed light on the co‐construction of joint Internet searches.
Keywords: Psychiatry and Mental health; Developmental and Educational Psychology; Social Psychology; Pediatrics; Perinatology and Child Health

Mobile Electroencephalography Reveals Differences in Cortical Processing During Exercises With Lower and Higher Cognitive Demands in Preadolescent Children - Becker, Linda; Büchel, Daniel; Lehmann, Tim; Kehne, Miriam; Baumeister, Jochen (Pediatric Exercise Science)
Purpose : The aim of this study was to examine whether cortical activity changes during exercise with increasing cognitive demands in preadolescent children. Method : Twenty healthy children (8.75 [0.91] y) performed one movement game, which was conducted with lower and higher cognitive demands. During a baseline measurement and both exercise conditions, cortical activity was recorded using a 64-channel electroencephalographic system, and heart rate was assessed. Ratings of perceived excertion and perceived cognitive engagement were examined after each condition. To analyze power spectral density in the theta, alpha-1, and alpha-2 frequency bands, an adaptive mixture independent component analysis was used to determine the spatiotemporal sources of cortical activity, and brain components were clustered to identify spatial clusters. Results : One-way repeated-measures analyses of variance revealed significant main effects for condition on theta in the prefrontal cluster, on alpha-1 in the prefrontal, central, bilateral motor, bilateral parieto-occipital, and occipital clusters, and on alpha-2 in the left motor, central, and left parieto-occipital clusters. Compared with the lower cognitive demand exercise, cortical activity was significantly higher in theta power in the prefrontal cluster and in alpha-1 power in the occipital cluster during the higher cognitive demand exercise. Conclusion : The present study shows that exercise complexity seems to influence cortical processing as it increased with increasing cognitive demands.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; Pediatrics; Perinatology and Child Health

Latent Congruence Model to Investigate Similarity and Accuracy in Family Members' Perception: The Challenge of Cross-National and Cross-Informant Measurement (Non)Invariance - Tagliabue, Semira; Zambelli, Michela; Sorgente, Angela; Sommer, Sabrina; Hoellger, Christian; Buhl, Heike M.; Lanz, Margherita (Frontiers in Psychology)
Several methods are available to answer questions regarding similarity and accuracy, each of which has specific properties and limitations. This study focuses on the Latent Congruence Model (LCM; Cheung, 2009), because of its capacity to deal with cross-informant measurement invariance issues. Until now, no cross-national applications of LCM are present in the literature, perhaps because of the difficulty to deal with both cross-national and cross-informant measurement issues implied by those models. This study presents a step-by-step procedure to apply LCM to dyadic cross-national research designs controlling for both cross-national and cross-informant measurement invariance. An illustrative example on parent–child support exchanges in Italy and Germany is provided. Findings help to show the different possible scenarios of partial invariance, and a discussion related to how to deal with those scenarios is provided. Future perspectives in the study of parent–child similarity and accuracy in cross-national research will be discussed.
Keywords: latent congruence model; measurement invariance; similarity; accuracy; cross-national; cross-informant; parent-child relationship; support exchanges

Intergenerational Value Similarity and Subjective Well-Being - Hoellger, Christian; Sommer, Sabrina; Buhl, Heike M. (Journal of Family Issues)
This investigation concentrates on the association of intergenerational value similarity and adult children’s and parents’subjective well-being, on the linkage between relationship quality and subjective well-being. Mediation effects of the relationship quality on the associations between value similarity and subjective well-being were focused. The sample consisted of 600 adult German children (53.8% women) and their parents. Dyadic correlations were constructed to determine the value similarity. In this study, the general value orientation and the family values were objects of research. We measured the subjective well-being with the Satisfaction with Life Scale and we used the Network of Relationships Inventory (NRI) to measure the relationship quality. Associations between subjective well-being and value similarity, and between subjective well-being and relationship quality, as well as mediation effects, were found. All effects depend on gender and perspective.
Keywords: adult child–parent dyads; relationship quality; life satisfaction; parent–child relationship; intergenerational stake hypothesis; mediation analyses

Ebenen der genetischen Analyse komplexer Phänotypen am Beispiel der Anorexia nervosa und der Varianz des Körpergewichts - Hirtz, Raphael; Zheng, Yiran; Rajcsanyi, Luisa S.; Libuda, Lars; Antel, Jochen; Peters, Triinu; Hebebrand, Johannes; Hinney, Anke (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie)
Zusammenfassung. Genetische Varianten beeinflussen die Gewichtsregulation und die Entwicklung von Essstörungen. Zunächst haben familienbasierte, sogenannte formalgenetische Studien den erblichen Anteil an der Gewichtsregulation und an der Ätiologie von Essstörungen beleuchtet. In einer Vielzahl von Studien zeigten sich sowohl für die Varianz des Körpergewichts als auch für die Entstehung von Essstörungen Erblichkeitsschätzer (Heritabilitätsraten) von über 50 %. Mit diesem Wissen begab man sich in den 90er-Jahren des letzten Jahrhunderts auf die Suche nach den zugrundeliegenden Genen (genauer: genetischen Varianten), die das Körpergewicht, das Essverhalten oder beide Phänotypen auf Grundlage geteilter Mechanismen beeinflussen. Zunächst wurden Kandidatengenstudien durchgeführt. Dabei untersuchte man auf Grundlage unterschiedlicher, v. a. aber pathophysiologisch plausibler Überlegungen Gene mit hoher Relevanz für die untersuchten Phänotypen. Dieser Ansatz war für Essstörungen nicht sehr erfolgreich, für die Gewichtsregulation konnte eine Handvoll Gene identifiziert werden. Verbunden mit großen methodischen Fortschritten in der genetischen Forschung und v. a. der Etablierung sogenannter genomweiter Assoziationsstudien (GWAS) Anfang der 2000er-Jahre konnten bislang über 1000 Varianten/Genorte detektiert werden, die das Körpergewicht beeinflussen. Für die Essstörung Anorexia nervosa (AN) sind aktuell acht solcher Genorte beschrieben. Diese Ergebnisse, aber auch aktuelle Ansätze zu phänotypübergreifenden Analysen lassen Einblicke in die komplexe Regulation des Körpergewichtes zu und haben zudem unerwartete Pathomechanismen für AN aufgezeigt.
Keywords: Psychiatry and Mental health; Clinical Psychology; General Medicine; Pediatrics; Perinatology and Child Health

Intergenerational Value Similarity in Adulthood - Hoellger, Christian; Sommer, Sabrina; Albert, Isabelle; Buhl, Heike M. (Journal of Family Issues)
This investigation concentrates on value similarity between parents and their children during adulthood. The interplay between gender, age, relationship quality, and frequency of contact on value similarity was analyzed. A total of 600 adult German children (53.8% women) and their parents took part in a questionnaire study. Value orientation was measured with a short version of Schwartz’s Portrait Values Questionnaire, and relationship quality with the Network of Relationships Inventory (Furman & Buhrmeister, 1992).Value similarity was higher in mother–daughter dyads compared to mother–son dyads, but in the other dyads, no significant differences were found. Regarding relationship quality, verbal intimacy was not related to value similarity. Parental satisfaction was associated with value similarity in the father–child dyads. Satisfaction, as perceived by adult children, was linked to value similarity in mother–child and father–son dyads. Furthermore, the frequency of contact related to value similarity between mothers and sons.
Keywords: Adult child–parent dyads; value similarity; relationship quality; frequency of contact; parent-child-relationship

Ethical Considerations of Applying Robots in Kindergarten Settings: Towards an Approach from a Macroperspective - Tolksdorf, Nils F.; Siebert, Scarlet; Zorn, Isabel; Horwath, Ilona; Rohlfing, Katharina J. (International Journal of Social Robotics)
In child–robot interaction (cHRI) research, many studies pursue the goal to develop interactive systems that can be applied in everyday settings. For early education, increasingly, the setting of a kindergarten is targeted. However, when cHRI and research are brought into a kindergarten, a range of ethical and related procedural aspects have to be considered and dealt with.While ethical models elaborated within other human–robot interaction settings, e.g., assisted living contexts, can provide some important indicators for relevant issues, we argue that it is important to start developing a systematic approach to identify and tackle those ethical issues which rise with cHRI in kindergarten settings on a more global level and address the impact of the technology from a macroperspective beyond the effects on the individual. Based on our experience in conducting studies with children in general and pedagogical considerations on the role of the institution of kindergarten in specific, in this paper,we enfold some relevant aspects that have barely been addressed in an explicit way in current cHRI research. Four areas are analyzed and key ethical issues are identified in each area: (1) the institutional setting of a kindergarten, (2) children as a vulnerable group, (3) the caregivers’ role, and (4) pedagogical concepts. With our considerations, we aim at (i) broadening the methodology of the current studies within the area of cHRI, (ii) revalidate it based on our comprehensive empirical experience with research in kindergarten settings, both laboratory and real-world contexts, and (iii) provide a framework for the development of a more systematic approach to address the ethical issues in cHRI research within kindergarten settings.
Keywords: Robot ethics · Kindergarten settings · Child–robot interaction · Early childhood education

Video analysis in Design-Based Research – Findings of a project on self-organised learning at a vocational school - Gössling, Bernd; Daniel, Desiree (EDeR. Educational Design Research)
The use of video analysis in Design-Based Research (DBR) seems to be promising, because the quality of video data matches the reality of educational fields. Educational fields are multidimensional and complex. And more than other types of data, video may capture, for example, the simultaneity of verbal and non-verbal interactions. This seems to be valuable in the quest for new insights and better designs of educational interventions. However, to date there has been limited use of video data in researching their design. This paper aims at reflecting how the benefits of video-based analysis may be utilised in DBR. Experiences with the collection and analysis of video data in a project to design self-organised learning (SOL) at a vocational school in Germany will be used as a case study to illustrate the type of findings that may feed into the DBR process. In this case, the project school had already introduced a sophisticated SOL model but was experiencing various implementation difficulties. Resolving issues like this requires insights into how exactly a concept is realised and what happens in the field. Therefore, video data on classroom interactions was gathered and sub-sequently analysed using the documentary method. This led to the reconstruction of two different types of orientation that were guiding the students when they dealt with their self-organised learning environment. In a subversive orientation, students playfully infiltrate the formal learning space with peer activities. In a confirming orientation, students stick to both, the (informal) rules of the (formal) learning arrangement and of the peer environment, thus expressing respect for the boundary between these two worlds. These findings have been used to redesign the SOL intervention.
Keywords: Pulmonary and Respiratory Medicine; Pediatrics; Perinatology and Child Health

Effects of Acute Physical Exercise With Low and High Cognitive Demands on Executive Functions in Children: A Systematic Review - Paschen, Linda; Lehmann, Tim; Kehne, Miriam; Baumeister, Jochen (Pediatric Exercise Science)
Purpose : Whereas many studies addressed the relation between acute physical exercise and executive functions (EF) in children, the effects of various modalities of acute exercise on EF still remain unclear. This systematic review investigated the effects of exercise with low and high cognitive demands on speed of processing and accuracy of performance in tasks examining inhibition, working memory, and cognitive flexibility in children. Method : A systematic literature research in electronic databases was performed. Controlled trials assessing the effects of acute exercise on EF in a pre–post design were included. Results : Ten studies involving a total of 890 participants revealed positive effects in working memory performance in speed of processing after acute exercises with low cognitive demands compared with seated rest, mixed results for inhibition after exercises with low and high cognitive demands, and mixed results for cognitive flexibility with low cognitive demands. Concerning accuracy, only mixed results were found for inhibition after exercises with low and high cognitive demands. Conclusion : The differentiated effects of acute exercises with low and high cognitive demands led to more positive effects in speed of processing compared with accuracy of performance. Further investigations including assessment of neurophysiological parameters of EF are needed.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; Pediatrics; Perinatology and Child Health

Co-development of manner and path concepts in language, action, and eye-gaze behavior - Lohan, Katrin S.; Griffiths, Sascha; Sciutti, Alessandra; Partmann, Tim C.; Rohlfing, Katharina (Topics in Cognitive Science)
In order for artificial intelligent systems to interact naturally with human users, they need to be able to learn from human instructions when actions should be imitated. Human tutoring will typically consist of action demonstrations accompanied by speech. In the following, the characteristics of human tutoring during action demonstration will be examined. A special focus will be put on the distinction between two kinds of motion events: path-oriented actions and manner-oriented actions. Such a distinction is inspired by the literature pertaining to cognitive linguistics, which indicates that the human conceptual system can distinguish these two distinct types of motion. These two kinds of actions are described in language by more path-oriented or more manner-oriented utterances. In path-oriented utterances, the source, trajectory, or goal is emphasized, whereas in manner-oriented utterances the medium, velocity, or means of motion are highlighted. We examined a video corpus of adult-child interactions comprised of three age groups of children-pre-lexical, early lexical, and lexical-and two different tasks, one emphasizing manner more strongly and one emphasizing path more strongly. We analyzed the language and motion of the caregiver and the gazing behavior of the child to highlight the differences between the tutoring and the acquisition of the manner and path concepts. The results suggest that age is an important factor in the development of these action categories. The analysis of this corpus has also been exploited to develop an intelligent robotic behavior -the tutoring spotter system-able to emulate children's behaviors in a tutoring situation, with the aim of evoking in human subjects a natural and effective behavior in teaching to a robot. The findings related to the development of manner and path concepts have been used to implement new effective feedback strategies in the tutoring spotter system, which should provide improvements in human-robot interaction.
Keywords: Imitation; Tutoring; Adult-child interaction; Human-robot interaction; Semantics; Teachable robots

Tutoring in adult-child-interaction: On the loop of the tutor's action modification and the recipient's gaze - Pitsch, Karola; Vollmer, Anna-Lisa; Rohlfing, Katharina; Fritsch, Jannik; Wrede, Britta (Interaction Studies)
Research of tutoring in parent-infant interaction has shown that tutors - when presenting some action - modify both their verbal and manual performance for the learner (‘motherese’, ‘motionese’). Investigating the sources and effects of the tutors’ action modifications, we suggest an interactional account of ‘motionese’. Using video-data from a semi-experimental study in which parents taught their 8 to 11 month old infants how to nest a set of differently sized cups, we found that the tutors’ action modifications (in particular: high arches) functioned as an orienting device to guide the infant’s visual attention (gaze). Action modification and the recipient’s gaze can be seen to have a reciprocal sequential relationship and to constitute a constant loop of mutual adjustments. Implications are discussed for developmental research and for robotic ‘Social Learning’. We argue that a robot system could use on-line feedback strategies (e.g. gaze) to pro-actively shape a tutor’s action presentation as it emerges.
Keywords: conversation analysis; interactional coordination; adult-child-interaction; feedback; gaze; quantification; social learning; motionese; tutoring

Mindful tutors: Linguistic choice and action demonstration in speech to infants and a simulated robot - Fischer, Kerstin; Foth, Kilian; Rohlfing, Katharina; Wrede, Britta (Interaction Studies)
It has been proposed that the design of robots might benefit from interactions that are similar to caregiver–child interactions, which is tailored to children’s respective capacities to a high degree. However, so far little is known about how people adapt their tutoring behaviour to robots and whether robots can evoke input that is similar to child-directed interaction. The paper presents detailed analyses of speakers’ linguistic and non-linguistic behaviour, such as action demonstration, in two comparable situations: In one experiment, parents described and explained to their nonverbal infants the use of certain everyday objects; in the other experiment, participants tutored a simulated robot on the same objects. The results, which show considerable differences between the two situations on almost all measures, are discussed in the light of the computer-as-social-actor paradigm and the register hypothesis.
Keywords: human–robot interaction (HRI); social communication; register theory; motionese; robotese; child-directed speech (CDS); motherese; mindless transfer; computers-as-social-actors

Can state-of-the-art saliency systems model infant gazing behavior in tutoring situations? - Narayan, Vikram; Lohan, Katrin Solveig; Tscherepanow, Marko; Rohlfing, Katharina; Wrede, Britta (Frontiers in Computational Neuroscience)
The behavior for a humanoid robot is often modeled in accordance with human behavior. Current research suggests that analyzing infant behavior as a basis for designing the robot behavior can guide us to a natural robot interface. Based on this idea many researchers support saliency systems as a bottom-up inspired way to simulate infant-like gazing behavior. In the field of saliency systems many different approaches have proposed and quantified in terms of speed, quality and other technical issues. But so far, no one compared and quantified them in terms of natural infant tutor interaction. The question we would like to address in this paper is: Can state-of-the-art saliency systems model infant gazing behavior in tutoring situations? By addressing these issues we want to take a step towards an autonomous robot system, which could be used more natural interaction experiments in future.
Keywords: child gazing behavior; computer vision; saliency; development

Language Does Something: Body Action and Language in Maternal Input to Three-Month-Olds - Nomikou, Iris; Rohlfing, Katharina (IEEE Transactions on Autonomous Mental Development)
Keywords: acoustic packaging; mother-child interaction; social learning; multimodal grounding in input; ecology of interactions; synchrony

On the loop of action modification and the recipient's gaze in adult-child interaction - Pitsch, Karola; Vollmer, Anna-Lisa; Fritsch, Jannik; Wrede, Britta; Rohlfing, Katharina; Sagerer, Gerhard (Gesture and Speech in Interaction)
Learning is a social endeavor, in which the learner generally receives support from his/her social partner(s). In developmental research – even though tutors/adults behavior modifications in their speech, gestures and motions have been extensively studied, studies barely consider the recipient’s (i.e. the child’s) perspective in the analysis of the adult’s presentation, In addition, the variability in parental behavior, i.e. the fact that not every parent modifies her/his behavior in the same way, found less fine-grained analysis. In contrast, in this paper, we assume an interactional perspective investigating the loop between the tutor’s and the learner’s actions. With this approach, we aim both at discovering the levels and features of variability and at achieving a better understanding of how they come about within the course of the interaction. For our analysis, we used a combination of (1) qualitative investigation derived from ethnomethodological Conversation Analysis (CA), (2) semi-automatic computational 2D hand tracking and (3) a mathematically based visualization of the data. Our analysis reveals that tutors not only shape their demonstrations differently with regard to the intended recipient per se (adult-directed vs. child-directed), but most importantly that the learner’s feedback during the presentation is consequential for the concrete ways in which the presentation is carried out.
Keywords: gaze; gesture; Multimodal; adult-child interaction

People modify their tutoring behavior in robot-directed interaction for action learning - Vollmer, Anna-Lisa; Lohan, Katrin Solveig; Fischer, Kerstin; Nagai, Yukie; Pitsch, Karola; Fritsch, Jannik; Rohlfing, Katharina; Wrede, Britta (Development and Learning, 2009. ICDL 2009. IEEE 8th International Conference on Development and Learning)
In developmental research, tutoring behavior has been identified as scaffolding infants' learning processes. It has been defined in terms of child-directed speech (Motherese), child-directed motion (Motionese), and contingency. In the field of developmental robotics, research often assumes that in human-robot interaction (HRI), robots are treated similar to infants, because their immature cognitive capabilities benefit from this behavior. However, according to our knowledge, it has barely been studied whether this is true and how exactly humans alter their behavior towards a robotic interaction partner. In this paper, we present results concerning the acceptance of a robotic agent in a social learning scenario obtained via comparison to adults and 8-11 months old infants in equal conditions. These results constitute an important empirical basis for making use of tutoring behavior in social robotics. In our study, we performed a detailed multimodal analysis of HRI in a tutoring situation using the example of a robot simulation equipped with a bottom-up saliency-based attention model. Our results reveal significant differences in hand movement velocity, motion pauses, range of motion, and eye gaze suggesting that for example adults decrease their hand movement velocity in an Adult-Child Interaction (ACI), opposed to an Adult-Adult Interaction (AAI) and this decrease is even higher in the Adult-Robot Interaction (ARI). We also found important differences between ACI and ARI in how the behavior is modified over time as the interaction unfolds. These findings indicate the necessity of integrating top-down feedback structures into a bottom-up system for robots to be fully accepted as interaction partners.
Keywords: robot simulation; hand movement velocity; robotic interaction partner; robotic agent; robot-directed interaction; multimodal analysis; Motionese; Motherese; intelligent tutoring systems; immature cognitive capability; human computer interaction; eye gaze; child-directed speech; child-directed motion; bottom-up system; bottom-up saliency-based attention model; adult-robot interaction; adult-child interaction; adult-adult interaction; human-robot interaction; action learning; social learning scenario; social robotics; software agents; top-down feedback structures; tutoring behavior

Development of a model describing individuated adult child-parent relationships - Buhl, Heike M. (International Journal of Behavioral Development)
This study investigates age-related changes and dyadic-specific differences in adult child–parent relationships. Using an individuation framework, two German samples of 224 and 105 participants aged between 21 and 47 years were administered the Network of Relationships Inventory, the Emotional Autonomy Scale and the Authority Reciprocity Questionnaire. Factor analyses resulted in a measurement model valid for adult children, their mothers and fathers. The model includes connectedness (with emotional and cognitive aspects) as well as individuality (assessed as power symmetry). Connectedness decreased with age. Symmetry in father–child relationships increased over time, while mother–child relationships were perceived to be symmetrical by early adulthood. Child–mother relationships were more connected than child–father relationships. Sons described themselves as more powerful than did daughters.
Keywords: adult child–parent relationships; adulthood; connectedness; Germany; individuation; symmetry

How can multimodal cues from child-directed interaction reduce learning complexity in robots? - Rohlfing, Katharina; Fritsch, Jannik; Wrede, Britta; Jungmann, Tanja (Advanced Robotics)
Robots have to deal with an enormous amount of sensory stimuli. One solution in making sense of them is to enable a robot system to actively search for cues that help structuring the information. Studies with infants reveal that parents support the learning-process by modifying their interaction style, dependent on their child's developmental age. In our study, in which parents demonstrated everyday actions to their preverbal children (8-11 months old), our aim was to identify objective parameters for multimodal action modification. Our results reveal two action parameters being modified in adult-child interaction: roundness and pace. Furthermore, we found that language has the power to help children structuring actions sequences by synchrony and emphasis. These insights are discussed with respect to the built-in attention architecture of a socially interactive robot, which enables it to understand demonstrated actions. Our algorithmic approach towards automatically detecting the task structure in child-designed input demonstrates the potential impact of insights from developmental learning on robotics. The presented findings pave the way to automatically detect when to imitate in a demonstration
Keywords: multi-modal motherese; child-directed input; motionese; learning mechanisms